'Rough sex' and the criminal law : global perspectives - Bows, Hannah; Herring, Jonathan (Feminist developments in violence and abuse, 2023)
Bows and Herring expertly collate an extensive mix of perspectives on the topic of 'rough sex' to contribute to a powerful feminist investigation of this critical and timely debate.